2006
DOI: 10.1073/pnas.0609184103
|View full text |Cite
|
Sign up to set email alerts
|

Zfp423 controls proliferation and differentiation of neural precursors in cerebellar vermis formation

Abstract: Malformations affecting the cerebellar vermis are only poorly understood at the genetic level. Dandy-Walker malformations (DWM) are characterized by dilation of the fourth ventricle, anterior rotation of the cerebellum, vermis hypoplasia or agenesis, and hydrocephalus, and they may occur together with other abnormalities (1). Recent work identified a subset of DWM patients carrying interstitial deletions on chromosome 3, most of which were hemizygous for both ZIC1 and ZIC4 (2), transcription factors that promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 31 publications
8
107
0
Order By: Relevance
“…5A). The outer proliferating zone (PZ) of the EGL contained the majority of BrdU-positive cells, consistent with BrdU incorporation into DNA of proliferating CGN precursors recently in S-phase (Alcaraz et al, 2006). The thickness of the PZ, defined by the lateral extent of the BrdU-positive cell nuclei, was unchanged between Scn1b wild-type and null mice (Fig.…”
Section: Inhibition Of Fgfr and Egfr Signaling Does Not Affect ␤1-medmentioning
confidence: 66%
“…5A). The outer proliferating zone (PZ) of the EGL contained the majority of BrdU-positive cells, consistent with BrdU incorporation into DNA of proliferating CGN precursors recently in S-phase (Alcaraz et al, 2006). The thickness of the PZ, defined by the lateral extent of the BrdU-positive cell nuclei, was unchanged between Scn1b wild-type and null mice (Fig.…”
Section: Inhibition Of Fgfr and Egfr Signaling Does Not Affect ␤1-medmentioning
confidence: 66%
“…Zfp423 is a newly identified transcription factor controlling proliferation and differentiation of neural precursors in cerebellar vermis formation. MYT1 is a transcription factor that has a role in the regeneration of oligodendrocyte lineage cells in response to demyelination (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…-/-mutants, we observed abnormal positioning of the preculminate fissure, resulting in reduction of the anterobasal domain in mutant cerebella. The relationship between cerebellar growth and foliation is complex as the two processes occur during roughly the same developmental period and are often both affected in cerebellar mutants (Alcaraz et al, 2006;Cheng et al, 2010;Corrales et al, 2006;Lewis et al, 2004;Satokata et al, 2000;Sillitoe and Joyner, 2007). Furthermore, analysis of conditional mutants in the Shh pathway has shown that reduction of Shh signaling produces a range of foliation phenotypes in addition to size deficits (Corrales et al, 2006).…”
Section: Research Articlementioning
confidence: 99%